TEACHING ACTIVITY LEARNING SYSTEM SCHEDULE SMA 79 JAKARTA USING MICROSOFT VISUAL FOXPRO 9.0 - Ningsih Maryana; Linda Wahyu Widianti, Skom, MMsi (Jurnal Sistem Informasi, 2008)
The school was established for the process of learning and teaching each student will be educated and guided by teachers to be able to behave politely and be more forward thinking. High School  Jakarta is the 79th country schools that have high discipline and good. Learning system SMA 79 Jakarta aims to facilitate the  performance of teachers at a school. Program designed to assist system  schedule of activities the students at the school, 79 high schools.  To create a  program such a system, the computer is a tool that is considered important.  Program  system of teaching and learning activities schedule 79 high schools was created using Microsoft Visual Foxpro 9.0. Because by using Microsoft Visual Foxpro 9.0 system of teaching and learning activities schedule 79 high schools became easier designed to utilize the various facilities provided by Microsoft  Visual Foxpro 9.0.  So the system is easy to use.